Hydrogen sulfide and its role in female reproduction - Pilsova, Aneta; Pilsova, Zuzana; Klusackova, Barbora; Zelenkova, Natalie; Chmelikova, Eva; Postlerova, Pavla; Sedmikova, Marketa (Frontiers in Veterinary Science, 2024)
Hydrogen sulfide (H2S) is a gaseous signaling molecule produced in the body by three enzymes: cystathionine-β-synthase (CBS), cystathionine-γ-lyase (CSE) and 3-mercaptopyruvate sulfurtransferase (3-MST). H2S is crucial in various physiological processes associated with female mammalian reproduction. These include estrus cycle, oocyte maturation, oocyte aging, ovulation, embryo transport and early embryo development, the development of the placenta and fetal membranes, pregnancy, and the initiation of labor. Despite the confirmed presence of H2S-producing enzymes in all female reproductive tissues, as described in this review, the exact mechanisms of H2S action in these tissues remain in most cases unclear. Therefore, this review aims to summarize the knowledge about the presence and effects of H2S in these tissues and outline possible signaling pathways that mediate these effects. Understanding these pathways may lead to the development of new therapeutic strategies in the field of women's health and perinatal medicine.